Design and Realization of Band Pass Filter in K-Band Frequency for Short Range Radar Application - Arie Setiawan; Taufiqqurrachman Taufiqqurrachman; Adam Kusumah Firdaus; Fajri Darwis; Aminuddin Rizal; Winy Desvasari; Hana Arisesa; Sulistyaningsih Sulistyaningsih; Prasetyo Putranto; Nasrullah Armi; Dharu Arseno (National Research and Innovation Agency, 2021)
Short range radar (SRR) uses the K-band frequency range in its application. The radar requires high-resolution, so the applied frequency is 1 GHz wide. The filter is one of the devices used to ensure only a predetermined frequency is received by the radar system. This device must have a wide operating bandwidth to meet the specification of the radar. In this paper, a band pass filter (BPF) is proposed. It is designed and fabricated on RO4003C substrate using the substrate integrated waveguide (SIW) technique, results in a wide bandwidth at the K-band frequency that centered at 24 GHz. Besides the bandwidth analysis, the analysis of the insertion loss, the return loss, and the dimension are also reported. The simulated results of the bandpass filter are: VSWR of 1.0308, a return loss of -36.9344 dB, and an insertion loss of -0.6695 dB. The measurement results show that the design obtains a VSWR of 2.067, a return loss of -8.136 dB, and an insertion loss of -4.316 dB. While, it is obtained that the bandwidth is reduced by about 50% compared with the simulation. The result differences between simulation and measurement are mainly due to the imperfect fabrication process.